Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1002/j.2168-9830.1998.tb00355.x
|View full text |Cite
|
Sign up to set email alerts
|

From the Students' Point of View: Experiences in a Freshman Engineering Design Course

Abstract: We evaluated the pilot semester of a freshman introduction to engineering course in order to provide an understanding of the students' experience in the course and identify aspects of this experience that could lead to improved student retention in engineering. The course concentrates on having students work in teams to identify customer needs, find solutions, and design and build a final product. We used qualitative research methods for data collection and analysis that included interviewing students using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 1 publication
0
48
0
Order By: Relevance
“…[9][10][11] Other research has shown that hands-on projects with context may contribute to deeper learning, particularly with women. [12] However our initial analysis of course-specific retention data does not clearly support this.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Other research has shown that hands-on projects with context may contribute to deeper learning, particularly with women. [12] However our initial analysis of course-specific retention data does not clearly support this.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, in our largest course (~1000 students per year out of 1200-1300 total engineering freshman), Introduction to Engineering and Design (Intro 160), students participate in lectures covering design topics that span multiple disciplines of engineering. In the laboratory section of this course, they work in teams of [8][9][10][11][12] to solve a real-world, client-based engineering design problem proposed mostly by individuals in the local community and industries. The other introduction to engineering courses (Intro 101 and 102) are much smaller (~100 students collectively), and do not have hands-on labs with client-based projects.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits include neatness, organization, quality and quantity of entries, and availability of the content to instructors, clients, and teammates. 2 LabArchives ELN was chosen due to the very successful implementation of the classroom version in the Department of Biomedical Engineering (BME) Design Courses, and the fact that our university began a campus-wide contract with LabArchives to provide this technology to research labs and other courses. LabArchives was well-studied and compared with numerous other ELNs and deemed the best option currently available that provided both a research and classroom edition.…”
Section: Electronic Laboratory Notebooksmentioning
confidence: 99%
“…This introductory freshman engineering course has been offered since 1994, and is highly valued by faculty and students. 2 In the laboratory section, they work in teams of 8-12 with a $200 budget (funded by our College of Engineering) to solve a real-world, client-based engineering design problem proposed mostly by individuals in the local community. Our regular clients often encourage others in the community to apply to our program.…”
Section: Introduction To Engineering Design Coursementioning
confidence: 99%
“…Academic training shows similar patterns, with "shy" or reticent students showing more difficulties in the classroom 8 . While the seminar students are engineers and scientists rather than physicians, similar principles hold true and similar remedies can be adapted and should be applicable 9,10 .…”
Section: General Backgroundmentioning
confidence: 99%